Relationship between structural and social dimensions of school culture - Čamber Tambolaš, Akvilina; Vujičić, Lidija; Jančec, Lucija (Frontiers in Education, 2023)
The culture of an educational institution is defined as a set of common beliefs and values that closely connect the members of a community. Structural dimensions (space, time, teaching materials, teaching strategies), social dimensions (relationships in the institution among school staff, between teachers and children, and among children), common rituals, and customs and traditions of the school are manifestations of school culture in which it is recognized and becomes visible. The research aim is to determine the connection between structural dimensions and social relations in the institution. The research was conducted in 2022 on a convenient sample of N=174 primary teachers employed in various schools in the Republic of Croatia. The Questionnaire for the Assessment of the Culture of the Educational Institution was used for data collection. An exploratory factor analysis on the Scale of the State of School Culture, which measured the state of structural dimensions, extracted two factors, based on which two subscales of good metric characteristics were created: Organization of educational work and Spatial and temporal dimensions. The Scale of the State of Relations in the Institution consists of 13 items and has a high reliability. In order to determine the existence of a connection between the structural and social dimensions of school culture, Pearson’s correlation coefficients were calculated. Moderate to relatively high positive correlations between the examined variables were found, which confirms the intertwining and interdependence of different dimensions of school culture, which significantly determines the quality of life and education of children in the institutional context.